Participation in local development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The 'A-Week' is an introductory course on participation in rural development offered by Agromisa, the Dutch support agency. The 'A-Week plus' is a second week, building on the A-Week but is practical, focussing on facilitating group processes and...